Exploring the effectiveness of problem- based learning (PBL) to improve the application of theory amongst tourism students. - Ramouthar, Shayna (The IIE, 2017)
Tourism and hospitality students struggle to apply their theoretical knowledge acquired in the actual workplace (Pan and Jamnia, 2014, p.36; Pez`ua and Bayardo, 2012, p.33). According to Clegg (2005, p. 415) tourism and hospitality employers deem that struggle with applying solutions to problems experienced in the industry. Problem Based Learning (PBL) is a learning pedagogy employed within the classroom to assist students to apply theory attained. In line with PBL pedagogy, students were presented with a case study depicting poor customer service in the tourism and hospitality. Based on the theory learnt, students were requested in groups to role play what they would have done to achieve good customer service if placed in that scenario. A cross sectional survey was employed to analyse the success of the PBL pedagogy. The findings of the study depicted that the PBL successfully promoted that integration of theory in the practical setting. Furthermore, the learning pedagogy showed to enhance students’ problem-solving skills.
Keywords: Problem based; Tourism industry; Hospitality industry; Problem solving skills